Monthly GDP estimates in Mexico based on the IGAE - Elizondo, Rocio (Estudios Económicos de El Colegio de México, 2019)
This article presents three methods to estimate the monthly GDP in Mexico: (1) a deterministic approach; (2) an extension of Denton method; and, (3) the Kalman filter. In these methods the monthly GDP is regarded as an unobservable variable that is approximated using only the IGAE. Results show that the three methods do a good job in adjusting the observed data of the quarterly GDP within the sample, with average adjustment errors of at most 0.1%. Additionally, given the dynamic structure of the Kalman filter method and that under different estimation periods it was found that the parameters corresponding remained relatively stable. Therefore, this method was used to perform out-of-sample forecasts.